Development and Validation of a Nomogram to Predict Distant Metastasis in Elderly Patients With Renal Cell Carcinoma - Wang, Jinkui; Zhanghuang, Chenghao; Tan, Xiaojun; Mi, Tao; Liu, Jiayan; Jin, Liming; Li, Mujie; Zhang, Zhaoxia; He, Dawei (Frontiers in Public Health, 2022)
Background: Renal cell carcinoma (RCC) is the most common renal malignant tumor in elderly patients. The prognosis of renal cell carcinoma with distant metastasis is poor. We aim to construct a nomogram to predict the risk of distant metastasis in elderly patients with RCC to help doctors and patients with early intervention and improve the survival rate. Methods: The clinicopathological information of patients was downloaded from SEER to identify all elderly patients with RCC over 65 years old from 2010 to 2018. Univariate and multivariate logistic regression analyzed the independent risk factors for distant metastasis in the training cohort. A nomogram was established to predict the distant metastasis of elderly patients with RCC based on these risk factors. The consistency index ( C-index ), calibration curve, and area under the receiver operating curve ( AUC ) were used to evaluate the accuracy and discrimination of the prediction model. Decision curve analysis ( DCA ) was used to assess the clinical application value of the model. Results: A total of 36365 elderly patients with RCC were included in the study. They were randomly divided into the training cohort ( N = 25321 ) and the validation cohort ( N = 11044 ). In the training cohort, univariate and multivariate logistic regression analysis suggested that race, tumor histological type, histological grade, T stage, N stage, tumor size, surgery, radiotherapy, and chemotherapy were independent risk factors for distant metastasis elderly patients with RCC. A nomogram was constructed to predict the risk of distant metastasis in elderly patients with RCC. The training and validation cohort's C-indexes are 0.949 and 0.954, respectively, indicating that the nomogram has excellent accuracy. AUC of the training and validation cohorts indicated excellent predictive ability. DCA suggested that the nomogram had a better clinical application value than the traditional TN staging. Conclusion: This study constructed a new nomogram to predict the risk of distant metastasis in elderly patients with RCC. The nomogram has excellent accuracy and reliability, which can help doctors and patients actively monitor and follow up patients to prevent distant metastasis of tumors.